Use of Noncontrast Computed Tomography and Computed Tomographic Perfusion in Predicting Intracerebral Hemorrhage After Intravenous Alteplase Therapy - Batchelor, Connor; Pordeli, Pooneh; d’Esterre, Christopher D.; Najm, Mohamed; Al-Ajlan, Fahad S.; Boesen, Mari E.; McDougall, Connor; Hur, Lisa; Fainardi, Enrico; Shankar, Jai Jai Shiva; Rubiera, Marta; Khaw, Alexander V.; et al. (Stroke (1970), 2017)
BACKGROUND AND PURPOSE—Intracerebral hemorrhage is a feared complication of intravenous alteplase therapy in patients with acute ischemic stroke. We explore the use of multimodal computed tomography in predicting this complication. METHODS—All patients were administered intravenous alteplase with/without intra-arterial therapy. An age- and sex-matched case–control design with classic and conditional logistic regression techniques was chosen for analyses. Outcome was parenchymal hemorrhage on 24- to 48-hour imaging. Exposure variables were imaging (noncontrast computed tomography hypoattenuation degree, relative volume of very low cerebral blood volume, relative volume of cerebral blood flow ≤7 mL/min ·per 100 g, relative volume of Tmax ≥16 s with all volumes standardized to z axis coverage, mean permeability surface area product values within Tmax ≥8 s volume, and mean permeability surface area product values within ipsilesional hemisphere) and clinical variables (NIHSS [National Institutes of Health Stroke Scale], onset to imaging time, baseline systolic blood pressure, blood glucose, serum creatinine, treatment type, and reperfusion status). RESULTS—One-hundred eighteen subjects (22 patients with parenchymal hemorrhage versus 96 without, median baseline NIHSS score of 15) were included in the final analysis. In multivariable regression, noncontrast computed tomography hypoattenuation grade (P<0.006) and computerized tomography perfusion white matter relative volume of very low cerebral blood volume (P=0.04) were the only significant variables associated with parenchymal hemorrhage on follow-up imaging (area under the curve, 0.73; 95% confidence interval, 0.63–0.83). Interrater reliability for noncontrast computed tomography hypoattenuation grade was moderate (κ=0.6). CONCLUSIONS—Baseline hypoattenuation on noncontrast computed tomography and very low cerebral blood volume on computerized tomography perfusion are associated with development of parenchymal hemorrhage in patients with acute ischemic stroke receiving intravenous alteplase.